EXAMINING DISPUTE SETTLEMENT UNDER THE ASEAN CHARTER: ANALYZES INDONESIA'S HANDLING OF VIOLATIONS IN THE AMBALAT BLOCK DISPUTE AND THE STATUS OF SIPADAN AND LIGITAN ISLANDS. - Maria Regina Sekar Kedaton Saputra (Problematika Hukum, 2024)
The territorial dispute between India and Malaysia over Pulau Sipadan, Pulau Ligitan and the Ambalat block is a major challenge to regional stability in Southeast Asia. Through conflicting historical and sovereignty claims, these disputes have undermined bilateral arbitration and led to international arbitration, particularly through the International Court of Justice (ICJ). These disputes, governed by international legal frameworks such as the Treaty on Certification and Cooperation (TAC) and the United Nations Convention on the Law of the Sea (UNCLOS), involve complex issues of maritime territorial delimitation and exploitation of resources. However, despite the ICJ decision, the decision-making process was complicated by difficulties in implementing the decision and enforcing the law, particularly with regard to the economic effects on oil and gas reserves. Addressing these challenges requires a multifaceted approach that emphasizes diplomatic dialogue, confidence-building, and strengthening regional cooperation. It is important to reduce problems, stabilize age and promote the well-being of all in South Asia. Effective conflict resolution is essential to maintaining regional peace and security and ensuring the continued progress and development of all parties involvedTerritorial disputes; Sipadan & Ligitan Island; ;International Court of Justice (ICJ); UNCLOS;Peaceful resolution